ANALISIS LAYANAN PENGUASAAN KONTEN TENTANG KESIAPAN BELAJAR PADA PESERTA DIDIK KELAS VIII SMP BUMI KHATULISTIWA KUBU RAYA - Octaviani, Nancy; Lestari, Sri; Endang, Busri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractContent mastery services are guidance and counseling services that provide assistance to individuals (students) both alone and in groups to master a particular content through learning activities.This study aims to analyze the content mastery service on students VIII of SMP Bumi Khatulistiwa Kubu Raya Year 2017. The method used is descriptive method and the form of research is survey form. The population in this study as many as 30 students. This research uses quantitative research. Data collection techniques used are direct communication in the form of interviews and indirect communication techniques in the form of questionnaires. Data analysis techniques using the formula percentage. Based on the results of data analysis of content mastery service research about readiness to achieve the score in the category of